2021
DOI: 10.1111/roie.12517
|View full text |Cite
|
Sign up to set email alerts
|

Trade and currency weapons

Abstract: We estimate the elasticities of exports to tariffs and to the real exchange rate within the same specification, allowing for a direct comparison.We find that tariffs have significantly more impact on exports than the real exchange rate, invalidating the symmetry assumption often made in macroeconomic models.From the point of view of short-term stabilization, tariffs and monetary policy can be considered as partly substitutes.Monetary policy is more stabilizing due to its internal transmission channels; at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 56 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…Bénassy‐Quéré et al (2021) estimated the exchange rate elasticity of exports by adding the natural logarithm of the BRER of economy i against economy j ,italiclnBRERitalicijt: italiclnXitalicijpt=italicβlnBRERitalicijt+λitalicipt+μitalicjpt+νitalicij+ϵitalicijpt …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bénassy‐Quéré et al (2021) estimated the exchange rate elasticity of exports by adding the natural logarithm of the BRER of economy i against economy j ,italiclnBRERitalicijt: italiclnXitalicijpt=italicβlnBRERitalicijt+λitalicipt+μitalicjpt+νitalicij+ϵitalicijpt …”
Section: Methodsmentioning
confidence: 99%
“…The exchange rate elasticity measures the percentage change in exports in response to the percentage change in the exchange rate. Bénassy‐Quéré et al (2021) summarized the exchange rate elasticities reported in several papers. In one study that they cited, Leigh et al (2017) investigated the exchange rate elasticities of exports for a large set of countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…We follow the approach of Bénassy-Quéré et al (2021) in investigating the relationship between exports, tariffs and exchange rates. They represented the exports of country i to country j of product p in year t, 𝑋 𝑖𝑗𝑝𝑡 with a series of fixed effects terms:…”
Section: Methodsmentioning
confidence: 99%